Lessons from Nature: Advances and Perspectives in Bionic Microwave Absorption Materials - Wang, Dashuang; Ping, Tuo; Du, Zhilan; Liu, Xiaoying; Zhang, Yuxin (Nano-Micro Letters, 2024)
Inspired by the remarkable electromagnetic response capabilities of the complex morphologies and subtle microstructures evolved by natural organisms, this paper delves into the research advancements and future application potential of bionic microwave-absorbing materials (BMAMs). It outlines the significance of achieving high-performance microwave-absorbing materials through ingenious microstructural design and judicious composition selection, while emphasizing the innovative strategies offered by bionic manufacturing. Furthermore, this work meticulously analyzes how inspiration can be drawn from the intricate structures of marine organisms, plants, animals, and non-metallic minerals in nature to devise and develop BMAMs with superior electromagnetic wave absorption properties. Additionally, the paper provides an in-depth exploration of the theoretical underpinnings of BMAMs, particularly the latest breakthroughs in broadband absorption. By incorporating advanced methodologies such as simulation modeling and bionic gradient design, we unravel the scientific principles governing the microwave absorption mechanisms of BMAMs, thereby furnishing a solid theoretical foundation for understanding and optimizing their performance. Ultimately, this review aims to offer valuable insights and inspiration to researchers in related fields, fostering the collective advancement of research on BMAMs. Highlights: 1 This review describes the classification of bionic objects of bionic wave-absorbing materials in detail. From marine organisms, insects, plants to animals, different bionic objects will bring diversified influences and applications. 2 The multifunctional applications of bionic microwave absorption materials are systematically introduced in this paper, from microwave absorption to anti-corrosion, to mechanics, electronics, wearable devices, etc. 3 The theoretical basis and simulation calculation of bionic microwave absorption materials are also discussed.